PERSPEKTIF IBU HAMIL TENTANG PERAN SUAMI DALAM PEMENUHAN GIZI SELAMA TRIMESTER I DI RB ERNITA TAHUN 2018 - Nia Desriva (STIKes Al-Insyirah Pekanbaru, 2019)
The role of a husband in fulfilling the nutrition of pregnant women is an indispensable action for a pregnant woman to prevent malnutrition in pregnant women and the birth of a baby with various risks and complications caused by complaints of nausea vomiting and increased emotions in the first trimester they experience. The purpose of this study was to determine the perspective of first trimester pregnant women about the role of husbands in fulfilling nutrition. The research design used in this study is qualitative phenomenology. The sampling technique used in this study was purposive sampling with 10 participants. Data collection is done by in-depth interviews using a recording device. The age of all participants ranged from 20-35 years. The majority of participants were in parity 1 (one). The majority of participants are Muslim. The majority of the participants' last education was high school. The majority of the ethnic groups participating in the husband are Javanese, and the majori ty of the participants' work is the IRT (Housewife). The results showed that there were four categories of expectant mothers' perspectives on the role of husbands in fulfilling nutrition during the first trimester, namely fulfilling the desires of the mother, serving mother's favorite food, accompanying the mother, reminding them to consume nutritious food. The results of the study showed that a small proportion of participants had supported the role of the husband. Therefore, it is expected that participants who have not supported or who have not felt the role of husbands, to better support the role of husbands so that husbands can better understand that the roles performed are very useful for mothers during the first trimester of pregnancy.